On-call geriatric psychiatry : handbook of principles and practice - Hategan, Ana; Bourgeois, James; Hirsch, Calvin H. (Springer, 2016)
This text covers basic principles and practice of on-call psychiatric care in the geriatric patient in various medical settings. It compiles the most likely complaints and provides assessment and management tools for each situation. Written and edited by expert geriatric psychiatrists, emergency psychiatrists, consultation/liaison psychiatrists, geriatricians, and other multidisciplinary specialists, this is the first handbook devoted to on-call geriatric psychiatry. Chapters contain an important summary of key points for managing clinical situations, case studies, and reflective questions. This text brings together relevant principles of on-call geriatric psychiatry provided in clinical settings such as emergency, acute and subacute inpatient, outpatient, residential, correctional, and consultation/liaison. It includes clinical topics such as psychopharmacology, psychotherapy, substance abuse, and includes coverage of medical ethics and the law, utilization of contemporary technology, and administrative and public health policy. On-Call Geriatric Psychiatry is the first practical guide to knit together evidence-based medicine and geriatric psychiatric principles and practice guidelines and is a valuable resource for trainees, psychiatrists, geriatricians, emergency departments, nursing home physicians, and other health professionals working with older adult patients.